Notched impact behavior of polymer blends: Part 1: New model for particle size dependence - Bucknall, C. B.; Paul, D. R. (Elsevier, 2009)
A model is proposed to explain the observed relationships between particle size and fracture resistance in high-performance blends, which typically reach maximum toughness at particle diameters of 0.2–0.4 μm. To date there has been no satisfactory explanation for the ductile–brittle (DB) transition at large particle sizes. The model is based on a recently developed criterion for craze initiation, which treats large cavitated rubber particles as craze-initiating Griffith flaws. Using this criterion in conjunction with Westergaard's equations, it is possible to map the spread from the notch tip of three deformation mechanisms: rubber particle cavitation, multiple crazing and shear yielding. Comparison of zone sizes leads to the conclusion that maximum toughness is achieved when the particles are large enough to cavitate a long way ahead of a notch or crack tip, but not so large that they initiate unstable crazes and thus reduce fracture resistance.
Keywords: Impact modified polymers; Toughening; Structure/property relationship